Memberikan Dorongan Atau Motivasi Dalam Bimbingan Belajar Siswa Di SD Negeri 096125 Tobasari - Usman Sidabutar; Putri Febriani Simamora; Nova Sinaga; Marta Manurung; Meri Sitinjak (Jurnal Nusantara Berbakti, 2023)
For students, it is one of the compulsory subjects that must be taken to train students to implement the knowledge and abilities they already have in a learning process according to their respective fields of study so that students get factual experience that can be used as a basis for developing themselves as prospective educators who are aware of their duties and responsibilities as academic staff in the world of education as mandated by the Merdeka Belajar curriculum.